Optimizing YouTube Videos Learning Media to Enrich Student’s Vocabulary at Seventh Grade Students - AT, Jurana; Latifa, Ammang; Amaluddin, Amaluddin (Edumaspul: Jurnal Pendidikan, 2023)
Various technological-based instruments and media have been used to help teachers and students achieve learning objectives, one of which is Youtube. It is an online platform that provides various videos that can be used as learning media and integrated into learning, especially English. Therefore, this research is focused on optimizing the use of youtube videos as learning media to enrich the vocabulary of the seventh-grade students of SMP Negeri 1 Duapitue. The research design administered was pre-experimental with one group pretest and posttest and involved 25 students as the research samples. The research instrument employed to obtain the students' vocabulary improvement was a vocabulary test in the form of multiple choice consisting of 20 items of questions. The results of the statistical analysis revealed an obvious improvement in the student's vocabulary mastery before and after giving the treatment.  This indicates that using youtube videos as learning media can increase the vocabulary of the seventh-grade students of SMP Negeri 1 Duapitue.